Sistem Fonologi Bahasa Ranau - Darsita, Darsita (Fakultas Adab dan Humaniora, UIN Syarif Hidayatullah Jakarta, Indonesia, 2004)
This paper will report about Ranau language, one af the world language that can be classifield as global languageÂ viability. This language represents a unique sound system such as the function of duration and intonation aredistinctive. This article also will describe about Ranau Phonology System. There are two subjects that willÂ be explaned: Firstly tries characterite al and any sounds that can be produced by the human vocal organs in the contextof spoken language, and dly to find vocal and consonant system.Â